Fundamentals of urine & body fluid analysis - Brunzel, Nancy A. MS, MLS(ASCP) (Elsevier, 2023)
Learn how to accurately analyze urine and body fluids with Fundamentals of Urine and Body Fluid Analysis, 5th Edition. Known for its clear writing style, logical organization, and vivid full-color illustrations, this renowned text offers the perfect level and depth of information for understanding the fundamental principles of urine and body fluids frequently encountered in the clinical laboratory. This includes the collection and analysis of urine, fecal specimens, vaginal secretions, and other body fluids such as cerebrospinal, synovial, seminal, amniotic, pleural, pericardial, and peritoneal fluids. Author Nancy Brunzel also shares her extensive knowledge and expertise in the field as she highlights key information and walks you through essential techniques and procedures--showing you how to correlate data with your knowledge of basic anatomy and physiology in order to understand pathologic processes